Images and artefacts of the ancient world (published for the British Academy by Oxford University Press, 2005)
The papers in this volume discuss how recent developments in imaging, image analysis, and image display/diffusion can be applied to three-dimensional objects of material culture from the classical world, ranging from inscribed writing tablets to buildings and urban sites